Peculiarities of forming multicultural competence in the process of training law students - Yanchyshyn , Volodymyr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article deals with the practical aspects of pedagogical training of lawyers' multicultural competence. Given the growing diversity of social relations and communication among future lawyers, they need to master the methods and techniques of effective communication and establishing trusting relationships with clients representing different cultures, ethno-religious and linguistic communities, and social strata. The author recommends a number of mechanisms for conducting practical classes (training sessions) for the development and practice of multicultural communication. Certain practical recommendations are aimed at assisting teacher educators in the process of training law students to apply multicultural competence in their professional activities. In conclusion, given the significant benefits of intercultural skills to a lawyer's intercultural competence, law student training should be offered as a minimum through an elective course, if not mandatory, in the curricula of all law schools across the country. As part of such a course, it is advisable to offer a set of seminar sessions in which professors can use the five skills of the Bryant and Peter methodology to teach law students how to interact with and solve problems that may arise in the course of working with different clients. Regardless of which model is used, intercultural competence skills should be taught in law schools.